Effects of Laser Peening with a Pulse Energy of 1.7 mJ on the Residual Stress and Fatigue Properties of A7075 Aluminum Alloy - Yuji Sano (MDPI AG, 2021)
Laser peening without coating (LPwC) using a palmtop-sized microchip laser has improved the residual stresses (RSs) and fatigue properties of A7075 aluminum alloy. Laser pulses with a wavelength of 1.06 μm and duration of 1.3 ns from a Q-switched Nd:YAG microchip laser were focused onto A7075 aluminum alloy samples covered with water. X-ray diffraction revealed compressive RSs on the surface after irradiation using laser pulses with an energy of 1.7 mJ, spot diameter of 0.3 mm, and density of 100–1600 pulse/mm2. The effects were evident to depths of a few hundred micrometers and the maximum compressive RS was close to the yield strength. Rotation-bending fatigue experiments revealed that LPwC with a pulse energy of 1.7 mJ significantly prolonged the fatigue life and increased the fatigue strength by about 100 MPa with 107 fatigue cycles. The microchip laser used in this study is small enough to fit in the hand or be mounted on a robot arm. The results may lead to the development of tools that extend the service life of various metal parts and structures, especially outdoors where conventional lasers are difficult to apply.